Theory of degrees, with applications to bifurcations and differential equations - Krawcewicz, Wiesław (Canadian Mathematical Society series of monographs and advanced texts, 1997)
The purpose of this book is to provide an introduction to degree theory and its applications to nonlinear differential equations. Two principles have guided the presentation and organization of this book.